Magnetic fluid sealing status estimation based on acoustic emission monitoring - Chen, Nuo; Li, Decai; Xue, Jinyu; Yin, Yuan; Li, Yanwen (Frontiers in Materials, 2022)
Analyzing acoustic emission (AE) signals generated in different magnetic fluid sealing processes to estimate the status of the seal. Based on a magnetic fluid rotary sealing experimental setup, the AE sensor is respectively attached to the shell at the corresponding position of the seal, and the external pressure is applied to the magnetic fluid seal by an air pump. As the pressure gradually increases, the magnetic fluid sealing rings under different pole teeth are gradually broken, and processes such as pressure transfer between the seal stages occur. These processes generate different AE signals, which are collected by the sensors. The results show that the root-mean-square value of AE signals generated at the moment of seal failure are different from those generated before and after. At the same time, by analyzing the characteristic values of AE signals generated in the whole process, we can infer the time when the rupture begins under different pole pieces, and further estimate the status of the magnetic fluid seal. For the first time, this study demonstrates the experimental and data analysis procedures of AE technology to magnetic fluid seals.